2022
DOI: 10.1002/wsb.1285
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of potential wild turkey nest predators in west‐central Louisiana

Abstract: Wild turkey nest success is variable spatially and temporally, with predation being the primary driver of nest loss. Historically, characteristics of nest site vegetation have been used to predict the probability of a nest being successful, a corollary to not being preyed upon. Implicit in nest success studies is that the density, distribution, and habitat preferences of predator species, relative to wild turkey nest distribution, drive the predation risk of nests on the landscape. We quantified diversity of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…While researchers often concentrate on characterizing nest sites, there is a tendency to neglect the critical aspect of movement decisions [ 22 ]. This neglects results in characteristics that frequently fail to describe the spatial scale at which nesting occurs [ 22 , 78 ] and are not clearly linked to nest success [ 20 , 40 ]. Our research highlights the biologically relevant spatial and temporal scale at which prospecting decisions influence nest fate.…”
Section: Discussionmentioning
confidence: 99%
“…While researchers often concentrate on characterizing nest sites, there is a tendency to neglect the critical aspect of movement decisions [ 22 ]. This neglects results in characteristics that frequently fail to describe the spatial scale at which nesting occurs [ 22 , 78 ] and are not clearly linked to nest success [ 20 , 40 ]. Our research highlights the biologically relevant spatial and temporal scale at which prospecting decisions influence nest fate.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have reported high rates of white-tailed deer fawn mortality due to predation, especially in the southeastern United States [31][32][33][34]. Additionally, coyote, bobcat, and gray fox depredation of turkey hens and poults during nesting and brood rearing periods [35][36][37] C. Ruth, South Carolina Department of Natural Resources, personal communication] may be partially responsible for declining wild turkey populations over the last decade [38][39][40][41]. Although these predators may predate hens, particularly during the spring [35][36][37][42][43][44], there is scant evidence across diet studies that they rely on wild turkeys as a food source [12,15,45].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, coyote, bobcat, and gray fox depredation of turkey hens and poults during nesting and brood rearing periods [35][36][37] C. Ruth, South Carolina Department of Natural Resources, personal communication] may be partially responsible for declining wild turkey populations over the last decade [38][39][40][41]. Although these predators may predate hens, particularly during the spring [35][36][37][42][43][44], there is scant evidence across diet studies that they rely on wild turkeys as a food source [12,15,45]. Better understanding of predator impacts on populations of wild turkeys and white-tailed deer is vital for agencies to effectively conserve and manage predator and prey species alike.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, avoidance of open-treeless areas and pine forest may be due to thermal regulatory constraints.Our results emphasize the complexity of how prior spatial processes can affect future events, such as nesting behavior. Researchers frequently measure and describe vegetative characteristics at and around nest sites, but these characteristics often fail to describe the spatial scale at which nesting is occurring (Deeming and Reynolds 2015,Ulrey et al 2022). Our research provides a biologically relevant spatial and temporal scale for evaluating nesting habitat.…”
mentioning
confidence: 98%